Antivax attitude in the general population along the autism-schizophrenia continuum and the impact of socio-demographic factors - Tarasi, Luca; Borgomaneri, Sara; Romei, Vincenzo (Frontiers in Psychology, 2023)
Introduction One of the most important inventions in human history is vaccines. However, to date a consistent amount of people exhibit a hesitant approach toward them and mixed results have emerged in the attempt to characterize which factors may play a role in predicting such negative attitude. Here, we aimed at investigating how the individual scoring along the autism-schizophrenic continuum component and socio-cultural factors contribute toward vaccination attitudes in the general population. Methods To test whether individual position along the autism-schizophrenic continuum could predict vaccine attitude, we used principal component analysis (PCA) to extract the component showing diametric loading between the Schizotypal Personality Questionnaire (SPQ) and Autistic Quotient (AQ) subscales. Then, we performed a series of multiple linear regression analyses to understand the relation between the ASD-SSD continuum component and Vax scores. We also included socio-demographic factors (i.e., gender, education level, and age) as predictors. Results Multiple regression analysis revealed that the closer the individual lied on the positive schizotypal pole, the higher was their negative attitude toward vaccines. A diametric, more favorable disposition was found for individuals closer to the autistic end of the continuum. Furthermore, we reported that among the socio-cultural factors, only age can be considered a significant predictor of vaccination attitudes, with younger participants showing a more positive attitudes toward vaccination, while the level of education is an important protective factor in mitigating the negative impact that the proximity to the SSD pole and age play against vaccination disposition. Discussion These findings are relevant to improve targeted public health interventions, highlighting the crucial role of demographic, psychological, and social correlates in predicting anti-vax beliefs, which have the devasting potential to increase the spread of infectious disease.